Spiritual Leadership Terhadap Kinerja Karyawan KSP CU Tri Tapang Kasih Sejiram Peran Mediasi Workplace Spirituality - Eriko, Marselinus Tio; Angga Hendharsa, Marselinus Tio Eriko Maulana Filani Rizal (Universitas Islam Kadiri, 2026)
Employee performance is a critical factor in determining organizational effectiveness and sustainability, particularly in microfinance institutions that rely heavily on human resource quality. This study aims to examine the effect of Spiritual Leadership on Employee Performance and to analyze the mediating role of Workplace Spirituality at KSP CU Tri Tapang Kasih Sejiram. The research employed a quantitative approach using a survey method. Data were collected from 124 employees selected through simple random sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that Spiritual Leadership has a positive and significant effect on Employee Performance and Workplace Spirituality. Furthermore, Workplace Spirituality positively and significantly influences Employee Performance. The mediation analysis reveals that Workplace Spirituality significantly mediates the relationship between Spiritual Leadership and Employee Performance. These findings suggest that the implementation of spiritual values in leadership practices can enhance employee performance both directly and indirectly by fostering a meaningful, harmonious, and spiritually supportive work environment.